2017
DOI: 10.1016/j.bbamem.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane topology of the arsenite permease Acr3 from Saccharomyces cerevisiae

Abstract: Acr3 is a plasma membrane transporter, a member of the bile/arsenite/riboflavin transporter (BART) superfamily, which confers high-level resistance to arsenicals in the yeast Saccharomyces cerevisiae. We have previously shown that the yeast Acr3 acts as a low affinity As(III)/H and Sb(III)/H antiporter. We have also identified several amino acid residues that are localized in putative transmembrane helices (TM) and appeared to be critical for the Acr3 activity. In the present study, the topology of Acr3 was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…According to some authors [98,127,128], the As(III) efflux system based in the arsenite permease Acr3p is the major detoxification pathway in yeasts. Homologues of Acr3 are particularly widespread in archaea, bacteria, unicellular eukaryotes, fungi, and lower plants, but are absent in flowering plants and animals [129]. In most of bacteria and archaea, the transporter ArsB carries out this function.…”
Section: Biotransformation and Resistance/tolerance To As In Fungi And Protistsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some authors [98,127,128], the As(III) efflux system based in the arsenite permease Acr3p is the major detoxification pathway in yeasts. Homologues of Acr3 are particularly widespread in archaea, bacteria, unicellular eukaryotes, fungi, and lower plants, but are absent in flowering plants and animals [129]. In most of bacteria and archaea, the transporter ArsB carries out this function.…”
Section: Biotransformation and Resistance/tolerance To As In Fungi And Protistsmentioning
confidence: 99%
“…Ycf1p could be a GSH conjugate transporter; it transports GSH-conjugated substrates across the vacuolar membrane, sequestering them within the vacuolar lumen [128]. flowering plants and animals [129]. In most of bacteria and archaea, the transporter ArsB carries out this function.…”
Section: Biotransformation and Resistance/tolerance To As In Fungi And Protistsmentioning
confidence: 99%
“…ACR3 transporter is a plasma membrane transporter, belonging to the bile/arsenite/riboflavin transporter (BART) superfamily, with 10 transmembrane (TM) segments and cytoplasmically oriented N-and C-terminal domain (Wawrzycka et al 2017). It is present in bacteria, archaeabacteria, fungi and in some plants, where it acts as the main As(III) efflux pump (Maciaszczyk-Dziubinska et al 2014).…”
Section: Acr3 (Arsenical Resistance 3) Transportermentioning
confidence: 99%
“…ACR3 exhibited As efflux capability to external environment, also reported by Daun et al (2012) in rice root. Cys151, Cys90 and Cys169 located in the fourth transmembrane span (TM4) and within the cytosolic loops of the transporter respectively are indispensable for full transport activity, while the hydrophilic loop connecting TM8 and TM9 is not involved in the transport activity (Wawrzycka et al 2017). Moreover, it has been suggested that the highly conserved residues Cys151 (TM4) and Ser349 (TM9) lie exactly within the intersection of the unwound fragments of the helices where they may form an As binding site.…”
Section: Acr3 (Arsenical Resistance 3) Transportermentioning
confidence: 99%
“…Amino acid mutagenesis gives structural information on a single position by modifying the particular residue using membrane-permeable and impermeable residue-specific chemical agents. Other approaches are N-glycosylation motif 25,26 (NXS/T where X can be any amino acid except proline) and epitope [27][28][29][30] insertion techniques, often employed for gathering topology data. N-glycosylation can only occur on the extra-cytosolic side of the membrane, and epitopes can be detected by specific antibodies, with or without permeabilization of the cell membrane.…”
mentioning
confidence: 99%